The CARDS toxin of Mycoplasma pneumoniae induces a positive feedback loop of type 1 immune response - Wang, Ting; Sun, Huiming; Lu, Zhitao; Jiang, Wujun; Dai, Ge; Huang, Li; Wang, Meijuan; Zhu, Canhong; Wang, Yuqing; Hao, Chuangli; Yan, Yongdong; Chen, Zhengrong (Frontiers in Immunology, 2022)
Background: Within the past 3-5 years, Mycoplasma pneumoniae has become a major pathogen of community-acquired pneumonia in children. The pathogenic mechanisms involved in M. pneumoniae infection have not been fully elucidated. Methods: Previous protein microarray studies have shown a differential expression of CXCL9 after M. pneumoniae infection. Here, we conducted a hospital-based study to explore the clinical significance of the type 1 immune response inflammatory factors interferon (IFN)-γ and CXCL9 in patients with M. pneumoniae pneumonia (MPP). Then, through in vitro experiments, we explored whether CARDS toxin stimulated F-DCs (dendritic cells incubated with Flt3L) to promote Th-cell differentiation; we also investigated the IFN-γ-induced CXCL9 secretion pathway in macrophages and the role of CXCL9 in promoting Th1 cell migration. Results: The CXCL9 expression level was upregulated among patients with a higher fever peak, fever duration of greater than 7 days, an imaging manifestation of lobar or segmental, or combined pleural effusion (P<0.05). The peripheral blood levels of IFN-γ and CXCL9, which were higher in patients than in the healthy control group, were positively correlated with each other (r=0.502, P<0.05). In patients, the CXCL9 expression level was significantly higher in the bronchoalveolar lavage fluid (BALF) than in the peripheral blood, and the BALF CXCL9 expression level was higher than that in the healthy control group (all P<0.05). Our flow cytometry analysis revealed that M1-phenotype macrophages (CD16+CD64+CD163−) were predominant in the BALF from children with MPP. In in vitro experiments, F-DCs stimulated with CARDS toxin promoted the differentiation of CD4+IFN-γ+ Th (Th1) cells (P<0.05). Moreover, IFN-γ induced high levels of CXCL9 expression in M1-type macrophages in a dose-dependent and time-dependent manner. Additionally, macrophages transfection with STAT1-siRNA-1 downregulated the expression of CXCL9 (P<0.05), and CXCL9 promoted Th1 cell migration (P<0.05). Conclusions: Our findings suggest that CARDS toxin induces a type 1 immune response positive feedback loop during M. pneumoniae infection; this putative mechanism may be useful in future investigations of immune intervention approaches for M. pneumoniae pneumonia.